PEMANFAATAN AGEN HAYATI TRICHO-KOMPOS DAN PGPR (Plant growth promotion rhizobactery) PADA PERTUMBUHAN VEGETATIF TANAMAN CABAI KERITING (Capsicum annuum L.) - Moh. Apriyadi Umbola; Edy Lengkong; Ronny Nangoi (COCOS, 2020)
ABSTRAK Chili (Capsicum annuum L.) is one of the horticultural commodities which is classified as a vegetable and is most widely cultivated in Indonesia. In addition, chilies contain minerals such as iron, potassium, calcium, phosphorus and niacin. Tricho-compost is a fertilizer derived from organic materials containing the antagonistic fungi Trichoderma sp. Tricho-compost as fertilizer is able to provide nutrients in the soil for plants. Plant Growth Promoting Rhizobacteria (PGPR) is a group of soil microorganisms that live and develop well in soils that are rich in organic matter and which are beneficial because they can spur plant growth and production. This study aims to determine the effect of the application of Tricho-compost and PGPR (Plant growth promotion rhizobactery) biological agents on the vegetative growth of chili plants. This research was conducted at the green house of the Faculty of Agriculture, Sam Ratulangi University (UNSRAT) Manado. The study lasted for 3 months using RAK (randomized block design) with 4 treatments, namely Control (NPK), Tricho-compost, PGPR (Plant Growth Promoting Rhizobacteria) and Tricho-compost added with PGPR (Plant Growth Promoting Rhizobacteria). Observation of growth parameters in the form of plant height, number of leaves, number of branches and stem diameter. Growth is carried out every week and starts at 2 week after transplanting until the plants are 2 months old. The results showed that the application of Tricho-compost and PGPR treatments given together gave the largest number of branches, number of leaves and stem diameter, while the parameters of height the largest plants were produced in the Tricho-compost treatment, although sta